Decision Support System for Achievement Scholarship Recipients at Vocational High Schools with the Analytical Hierarchy Process Method - Irfan Turahman (Engineering: Journal of Mechatronics and Education, 2024)
In SMK Negeri 2 BIMA, there is a scholarship program, but the process of giving is still running manually and subjectively. The system used is still not computerized, so at the time of selection, the scholarship recipients are directly selected without specific criteria, which could be based on family relationships. So, there is a weakness in the current system running, one of which is less precisely the distribution of scholarships. This happened because it was influenced by the amount of data the incoming scholarship recipients entered. Therefore, a system that can jointly assist the school in decision-making based on these criteria is needed. The AHP algorithm is the basis of decision-making to determine the students who excel in the system to be built. Analytical Hierarchy Process (AHP) provides convenience with multiple criteria assessments with a framework of thinking that uses a hierarchical process which then calculates the weight for each criterion in determining the eligibility of students who will receive achievement scholarships. The results of this study are expected to help SMK 2 Bima decide which students are more entitled to receive outstanding scholarships. The output generated from this system is in the form of a ranking of prospective scholarship recipients.